2016
DOI: 10.1308/rcsann.2016.0058
|View full text |Cite
|
Sign up to set email alerts
|

Safe management of paediatric penetrating head injury without a CT scanner: A strategy for humanitarian surgeons based on experience in southern Afghanistan

Abstract: INTRODUCTION In many parts of the world, access to a CT scanner remains almost non-existent, and patients with a head injury are managed expectantly, often with poor results. Recent military medical experience in southern Afghanistan using a well-equipped surgical facility with a CT scanner has provided new insights into safe surgical practice in resource-poor environments. METHODS All cases of children aged under 16 years with penetrating head injury who were treated in a trauma unit in southern Afghanistan b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Antibiotic therapy should be initiated on admission [25] [40] [41]. Antibiotic therapy is the best barrier to pre-or post-operative infection, which can be a cause of mortality [9] [44]. In our study our attitude was identical to that reported in the publications literature.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Antibiotic therapy should be initiated on admission [25] [40] [41]. Antibiotic therapy is the best barrier to pre-or post-operative infection, which can be a cause of mortality [9] [44]. In our study our attitude was identical to that reported in the publications literature.…”
Section: Discussionsupporting
confidence: 68%
“…Location The location of PCCWs varied from study to study independently of the circumstances in which they occurred [23] [25] [31] [32]. However, the main loca-tions were frontal [13] [19] [33], parietal [9] [25] or frontaloparieto-temporal [7]. The position of the victims at the time of contact and the virulence of the aggression seem to be determining factors in the predominance of localizations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation